Financial Risk Management Strategies for Multinational Corporations: Hedging Against Currency and Interest Rate Fluctuations - Purwati, Purwati; Hidayat, Muhammad (Penelitian dan Pengembangan Ilmu, 2024)
This research explores the application of behavioral finance principles in financial risk management strategies adopted by multinational companies, with a focus on hedging against currency and interest rate fluctuations. Using a systematic literature review (SLR) approach, this study analyzes existing literature to identify how cognitive biases influence hedging decisions and how behavioral finance principles are applied in this context. The main findings show that biases such as overconfidence, loss aversion significantly influence hedging decisions, which often lead to suboptimal decisions. Additionally, the application of these principles varies by industry sector and geographic region. This research identifies the need for more comprehensive theoretical models and analytical tools to address cognitive biases, and suggests further empirical research to quantify the impact of psychological biases on long-term financial performance. The conclusions of this study emphasize the importance of integrating psychological factors in risk management strategies to increase the effectiveness and financial resilience of multinational companies.